Diversity and conservation status of selected rare and endemic limestone orchid species in Padawan, Sarawak - Khor, Hong Eng (2012)
Padawan Limestone Formation is located at the south of Kuching, Sarawak, bordering with Kalimantan, which is the largest outcrop of Sarawak. The favourable unique climate and ecological conditions providing a suitable environment for the plants enhance the rich diversity and high endemism in the limestone hills, especially the orchids. The limestone orchids in Padawan are not only threatened by the over collection by hobbyists and enthusiasts, but the habitat is also threatened with deforestation and quarrying activities. Furthermore, the orchid diversity was poorly studied and the information of rare and endemic species was very limited due to the inaccessibility in the area. Hence, a diversity study was conducted on the Orchidaceae in the limestone hills of Padawan with the objectives to document the macromorphological taxonomic characters of the limestone orchids, to study the diversity of limestone orchids, to determine the diversity indexes for conservation purposes and to evaluate conservation status of rare and endemic species in Padawan, Sarawak. Field sampling collections were done at 42 limestone localities in a sustainable manner. Collection of specimens for living collections and herbarium specimens were prepared. The taxonomic characters of collected specimens were documented and described in details for identification and classification. Quadrate plots of 10 x 10 m were established at 20 selected sites to investigate the diversity indexes. A total of 273 species from 70 genera were recorded from this study. This encompassed 29.7% of Sarawak’s orchids in Padawan limestone area measuring approximately 436.6 km2 (0.0035% of Sarawak land area). From the study, 57 species were new records in Padawan, 38 species were new records to Sarawak and 15 species were new records to Borneo Island by comparison to the list by Beaman et al. (2001), Rusea et al. (2007) and World Checklist of Selected Plants (2012). The diversity of the limestone hills was shown to be high with Simpson’s Diversity Index (D=0.94), Shannon-Weiner’s Diversity Index (H=2.87) and Evenness Index (J=0.92) from the quadrate plots. The diversity richness was very high with a mean of 31 species and plant density of 1.5 plant per m2 in the plots. Sixteen endemic orchids, which included 2 narrow endemic species in Sarawak limestone, 8 endemic in Borneo, and 6 endemic in Malesia region were identified. From the identified rare and endemic species, 10 species were classified as Endangered species, 2 as Vulnerable species and 4 as Near Threatened in accordance to the IUCN Red List Categories and Criteria Version 3.1.